Analysis of Supervision of Notary Positions by MPN Based on Law Number 2 of 2014 in Tangerang Regency - Pramudita, Reta; Lesmana, Sri Jaya; Indayatun, Ratna (The International Journal of Law Review and State Administration, 2025)
Notary is a position that carries out some of the public functions of the state in the field of private law and carries out a role in making authentic deeds. Supervision is carried out to prevent irregularities and protect the public from possible legal violations. The aim of this research is to assess how the Regional Notary Supervisory Council in Tangerang Regency has implemented notary supervision. The findings of this research show how important the supervision of the Regional Notary Supervisory Council is in maintaining the integrity of the notary profession. However, there are obstacles to the inspection process, such as the large number of Notaries and the need to organize an effective supervision schedule. Additionally, inadequate funding is another element that reduces the effectiveness of supervision. The Regional Notary Supervisory Council carries out supervision through routine reports and periodic supervision, as well as receiving complaints from the public. Despite facing challenges, such as a slow complaint process and a lack of understanding by Notaries, the assembly remains committed to carrying out its duties. This research aims to increase our understanding of notary supervision and expand public understanding of the process.